2010
DOI: 10.1016/j.ygyno.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The extrinsic apoptosis pathway and its prognostic impact in ovarian cancer

Abstract: Fas and TRAIL loss is associated with dedifferentiation and worse prognosis. Expression of DR4, DR5, caspase 8 and c-FLIP by most ovarian cancers does not correlate with survival. High c-FLIP expression should be taken into account for death receptor targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…FASLG, encoding Fas ligand, was not found to have a prognostic role in OC at the protein level [36], similar to the mRNA data in the present study.…”
supporting
confidence: 90%
“…FASLG, encoding Fas ligand, was not found to have a prognostic role in OC at the protein level [36], similar to the mRNA data in the present study.…”
supporting
confidence: 90%
“…23 On the other hand, the caspase-8 is activated after the formation of death-inducing signaling complex (DISC) and cleaves different apoptotic proteins, resulting in execution of apoptosis. 24 This caspase is involved in both extrinsic and intrinsic pathways of apoptosis and acts via caspase-3 and Bid proteolytic cleavage. It was indicated that caspase-8 is inactivated in many human cancers, which may cause tumor progression and resistance to chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of FADD-like IL-1b-converting enzyme-like apoptotic protein-inhibitory protein (c-FLIP) and subsequent suppression of its anti-apoptotic effect is another mechanism of action of many chemo-and/or radiotherapeutic agents against various types of cancer [68, [130][131][132][133]. Indeed, the modulation of c-FLIP function can be another interesting target for anti-cancer therapy, as indicated by Pawar et al After demonstrating that the interaction between calmodulin and c-FLIP contributes to the anti-apoptotic effect of FLIP, since the abrogation of such interaction via the use of calmodulin antagonists results in increased apoptosis in cholangiocarcinoma cells, they have recently reported that the calmodulin antagonist tamoxifen inhibits cholangiocarcinoma tumorigenesis in nude mice, and so they suggest that tamoxifen may be used as a therapy for cholangiocarcinoma and maybe other malignancies in which this mechanism plays a role in the tumor pathogenesis [134].…”
Section: Modulation Of Other Members Of the Pathwaymentioning
confidence: 99%